NCAPG as a Novel Prognostic Biomarker in Glioma - Jiang, Xiulin; Shi, Yulin; Chen, Xi; Xu, Haitao; Liu, Bohu; Zhou, Fan; Huang, Xiaobin; Cho, William C.; Li, Lihua; Pu, Jun (Frontiers in Oncology, 2022)
ABSTRACT Background: The function of non-SMC condensin I complex subunit G (NCAPG) has been explored in various cancers. However, the prognostic value and biological functions of NCAPG in low-grade glioma (LLG) and the correlation with the immune cell infiltrate have not been reported. This study aimed to determine the biological function of NCAPG in LGG and to evaluate the correlation between NCAPG and LGG progression. Methods: Clinical information for LGG patients was obtained from TCGA, CGGA, GEO, Rembrandt, and Gravendeel databases. We examined the correlation between NCAPG expression, clinical-pathological characteristics, and clinical outcome. Furthermore, we uncovered the correlation between NCAPG and immune cell infiltration in LGG. Finally, we examined the function of NCAPG in the progression of LGG. Results: In this study, we discovered that NCAPG expression was higher in LGG tissue compared to adjacent tissues. Higher expression of NCAPG was correlated with a poor prognosis, worse histological features, IDH mutation status, 1p19q deletion status, and chemoradiotherapy status. Univariate and multivariate Cox analysis demonstrated that tumor grade, age, IDH mutation status, 1p19q status, and NCAPG expression may be independent prognostic factors in LGG patients. The constructed prognostic models performed well for the prediction of OS, DSS, and PFS using NCAPG expression as a predictive variable. Furthermore, the analysis of immune cell infiltration indicated that high expression of NCAPG was correlated with infiltration of various immune cells and sensitivity to cancer drugs. GSEA enrichment analyzes suggested that high NCAPG expression was mainly involved in cell proliferation and the immune response-related signaling pathway. Finally, we determined that NCAPG knockdown significantly reduced cell survival, proliferation, and migration abilities of LGG. Conclusion: These findings demonstrated that NCAPG expression is correlated with LGG progression and immune infiltration in LGG and may represent a useful prognostic biomarker.